Crustal evolution of the amphibolite- to granulite-facies transition zone in the eastern Dharwar Craton, southern India: insight from petrological modelling, zircon U–Pb geochronology and Hf isotopes - Maibam, B; Palin, RM; Gerdes, A; White, RW; Berndt, J; Foley, S; Goswami, JN (Wiley, 2023)
Integrated petrological, geochemical, isotopic and thermobarometric study of metasedimentary rocks from the amphibolite- to granulite-facies transition zone of the Eastern Dharwar Craton (EDC), South India, has provided new insight into the evolution of the lower continental crust in this region. Phase equilibrium modelling of metapelites and metagreywackes suggests that they reached peak metamorphism at ~800–850°C and 6–7 kbar (corresponding to a paleodepth of ~20 km), with minor retrograde change occurring at ~700°C and 3–5 kbar during exhumation. U–Pb ages of conventionally separated zircon from metapelite samples range from 2.5 to 3.4 Ga, whereas garnet-hosted zircons yield younger ages of 2.5–2.7 Ga. Zircon Th/U ratios and Hf isotopes reveal several significant pulses of zircon growth at 3.0, 2.95 and 2.7 Ga. Hf isotope data suggest the evolution of juvenile magma at around 3.2 Ga, while Hf model ages show that the crust building process also involved the recycling of pre-existing Mesoarchean crust. Our study confirms the presence of a Paleoarchean component in the EDC lower crust, as well as older metamorphic events in the terrain and the gradational distribution of the metamorphic rocks.